The Senolytic Drug Fisetin Attenuates Bone Degeneration in the Zmpste24−/− Progeria Mouse Model - William S. Hambright; Xiaodong Mu; Xueqin Gao; Ping Guo; Yohei Kawakami; John Mitchell; Michael Mullen; Anna-Laura Nelson; Chelsea Bahney; Haruki Nishimura; Justin Hellwinkel; Andrew Eck; et al. (Journal of Osteoporosis)
Aging leads to several geriatric conditions including osteoporosis (OP) and associated frailty syndrome. Treatments for these conditions are limited and none target fundamental drivers of pathology, and thus identifying strategies to delay progressive loss of tissue homeostasis and functional reserve will significantly improve quality of life in elderly individuals. A fundamental property of aging is the accumulation of senescent cells. Senescence is a cell state defined by loss of proliferative capacity, resistance to apoptosis, and the release of a proinflammatory and anti-regenerative senescence-associated secretory phenotype (SASP). The accumulation of senescent cells and SASP factors is thought to significantly contribute to systemic aging. Senolytics—compounds which selectively target and kill senescent cells—have been characterized to target and inhibit anti-apoptotic pathways that are upregulated during senescence, which can elicit apoptosis in senescent cells and relieve SASP production. Senescent cells have been linked to several age-related pathologies including bone density loss and osteoarthritis in mice. Previous studies in murine models of OP have demonstrated that targeting senescent cells pharmacologically with senolytic drugs can reduce symptomology of the disease. Here, we demonstrate the efficacy of senolytic drugs (dasatinib, quercetin, and fisetin) to improve age-associated degeneration in bone using the Zmpste24−/− (Z24−/−) progeria murine system for Hutchinson–Gilford progeria syndrome (HGPS). We found that the combination of dasatinib plus quercetin could not significantly mitigate trabecular bone loss although fisetin administration could reduce bone density loss in the accelerated aging Z24−/− model. Furthermore, the overt bone density loss observed in the Z24−/− model reported herein highlights the Z24 model as a translational model to recapitulate alterations in bone density associated with advanced age. Consistent with the “geroscience hypothesis,” these data demonstrate the utility of targeting a fundamental driver of systemic aging (senescent cell accumulation) to alleviate a common condition with age, bone deterioration.